Cocriação de valor e seus efeitos no turismo considerando a tendência de maximização - Ribeiro, Thiago de Luca Sant’Ana (2022)
Value co-creation has received the attention of several researchers as an overarching concept that describes collaboration between various stakeholders and in different contexts. In this thesis, we developed three interdependent studies seeking to understand the conceptual-theoretical evolution of value co-creation in tourism and its empirical effects in complex models, including mediation and moderation variables. Study I identified the conceptual-theoretical evolution of value co-creation in tourism, based on a systematic literature review, which systematized knowledge from three perspectives: a) methodological, b) thematic and c) theoretical (relationships in advance, consequence, mediation and moderation involved in value co-creation). Study II analyzed the mediating effect of value co-creation in relation to engagement and recommendation in tourism. In addition, it analyzed the direct effects of value co-creation on recommendation and engagement on recommendation and value co-creation. Finally, study III analyzed through an experiment stimulating engagement (high and low) and value co-creation (high and low) the moderating role of the maximization tendency in the relationship between value co-creation and its effects on satisfaction, recommendation and purchase intention in tourism. It also analyzed the mediating effect of value co-creation on the relationship between engagement and behavioral intentions. Among our main findings from Study I, we found that by 2019 most articles published on value co-creation were qualitative and focused on stakeholders, being surpassed only by quantitative ones in 2020, with a focus on tourists. The thematic analysis identified five main clusters focusing on a) management, b) consumer experience, c) consequences of value co-creation, d) social media and e) branding. The theoretical analysis identified interaction, engagement and prior knowledge as the main antecedents of value co-creation, and satisfaction, loyalty and well-being as the main consequences. We found few studies with complex models that included value co-creation as a mediating or moderating variable. Among our main findings from Study II, we found that co-creation of value in an experiential context partially mediates the relationship between consumer engagement and recommendation. We also found that both engagement and value co-creation have direct positive effects in relation to recommendation. Finally, among our main findings from Study III, we found that the maximization trend in a purchase personalization context negatively moderates the relationship between value co-creation and satisfaction and between value co-creation and recommendation. We also found that value co-creation fully mediates the relationship between engagement and behavioral intentions. There is no direct effect between engagement and behavioral intentions and there is also no moderating effect of the maximization tendency on the relationship between value co-creation and purchase intention.